(untitled) (Research, Society and Development, 2020)
In Brazilian dairy sheep, some production rates, such as weight gain of lambs, are below expectations, and alternative ingredients such as powdered egg can optimize the performance in dairy lambs. Therefore, this study aimed to estimate the average daily gain (ADG), feed efficiency, and blood parameters of lambs that were supplemented with powdered eggs during the suckling period. Twenty Lacaune lambs were used, distributed in four treatments: the checking (without using powdered egg), the inclusion of 5% powdered egg, the inclusion of 10% powdered egg and, the inclusion of 15% powdered egg in the liquid diet. For performance evaluation, the animals were weighed weekly, and daily food and leftovers were also weighed to determine feed efficiency. Blood samples were collected to measure albumin, urea, total proteins, cholesterol, and triglycerides. The ADG and feed efficiency data were subjected to a regression analysis at the 5% probability level. The serum data were analyzed according to a completely randomized design, and the means were compared by Tukey’s test at a significance level of 5%. The ADG results showed quadratic behavior for the gain curve, which indicates that lambs supplemented with 15% powdered egg obtained ADG superior to other treatments (P<0.05). In serum biochemistry, the parameters that obtained differences between treatments were albumin (P=0.0004), urea (P=0.0338) and, cholesterol (P=0.0277), with greater expressiveness in animals that received higher levels of powdered egg inclusion. Consequently, it is possible to infer that the inclusion of 15% powdered egg during the suckling of Lacaune lambs significantly improves weight gain and increases serum levels of albumin, urea and, cholesterol in animals.